PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA GURU DENGAN MEDIASI KOMITMEN ORGANISASIONAL (STUDI GURU PAUD FORMAL DI KABUPATEN REMBANG) - Siti Kasmirah, 1142020137 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study to pupose the effect of teacher individual characteristics and job characteristics on performance by mediating organizational commitment (studies in early childhood education teachers in the district Rembang ). The research was conducted on early childhood education in the District of Starch penddik 156 people. Sample taking the entire population for the research sample . Analysis of the validity of the test data using the components of the matrix , Cronbach alpha reliability test , multiple regression analysis , t test and test with an adjusted r 2 r square. Results reveal that the competence effect on organizational commitment . Positive effect on the employment characteristics of organizational commitment .Iindividual characteristics has a positive effect on the performance of early childhood educators. Job characteristics affect employee performance early childhood educators . Organizational commitment has a positive effect on the performance of early childhood educators. Organizational commitment did not mediate the effect of Individual characteristics on the performance of early childhood educators. Organizational commitment did not mediate the effect of job characteristics on the performance of early childhood educators. Keywords : Individual characteristics, job characteristics, organizational commitment and performance